Eugenia uniflora L. Leaf Extract Ameliorated Metabolic Traits and Reduced Visceral Adiposity in Rat Model of Metabolic Syndrome (Bangladesh Journal of Medical Science, 2026)
Background The prevalence of metabolic syndrome has risen globally in recent years. Visceral fat and insulin resistance have been reported as crucial factors for chronic inflammation that caused several complications of metabolic syndrome. Pitanga (Myrtaceae) are extensively dispersed and have long been utilized as herbal treatments and reported to have antioxidant and antidiabetic activities. Objective Investigate the activities of Eugenia uniflora L. leaf extract on the metabolic syndrome components: epididymal fat and pancreas histology in a rat model. Method The experiment followed a post-test only design using 25 male Wistar rats. The animals were randomly allocated into five equal groups: normal, metabolic syndrome (MS), MS + telmisartan 8 mg/kg as standard treatment; MS + Eugenia uniflora L. leaf extract (ELE) 50 mg/kg; and MS + ELE 100 mg/kg. Metabolic syndrome was induced by high-fat diets and 20% fructose in drinking water for 8 weeks simultaneously with standard treatment and extracts. At day 57, metabolic syndrome components were measured, and epididymal fat as well as the pancreas were taken for histological analysis. Results Administration of ELE 100 mg/kg improved metabolic syndrome components, including reduced blood glucose, reduced blood triglycerides, reduced systolic blood pressure, reduced Lee Index, and increased HDL-cholesterol. The ELE 100 mg/kg also reduced epididymal adipocyte area, and the result was comparable with telmisartan. However, neither telmisartan nor ELE affected the size of pancreatic islets. Conclusion ELE improves metabolic syndrome components and reduces visceral adiposity in rat models induced by HFD and fructose combination.Bangladesh Journal of Medical Science Vol. 25 No. 03 July’26 Page: 764-776